Manajemen Pembelajaran Pendidikan Agama Islam Melalui Program Pelaksanaan Sholat Dhuha di SMP IT Ad Durrah - Panjaitan, M. Adimas Juanda; Mario Kasduri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the management of Islamic religious education learning through the dhuha prayer implementation program at smp it ad durrah. The method used in this study is descriptive qualitative research with data collection techniques in the form of in-depth direct observation, interviews and documentation. The location used as the object of study at SMP IT Ad Durrah. In this study, four data analyses were used, namely data collection, data reduction, data presentation and conclusion drawing. The research findings show that principals and religious teachers plan religious learning through curriculum development and meetings. Religious learning through habituation of dhuha prayers at AD DURRAH IT Junior High School is carried out with good management. This is indicated by the enthusiasm of the students to do wudhu and perform dhuha prayers. Dhuha prayers are performed in Islamic Education subjects. Dhuha prayers are performed by students in grades 1 to 3 of junior high school. However, the place of worship is inadequate. Evaluation is routinely carried out at teacher meetings. The conclusion of this study is that the management of Islamic religious education learning through the dhuha prayer implementation program at AD durrah IT Junior High School provides important learning to students and provides continuous learning for them so as to give birth to religious students not only carrying out the obligatory but living the Sunnah of the Prophet.